Thermodynamics of the air–qater interface of mixtures of surfactants with polyelectrolytes, oligoelectrolytes, and multivalent metal electrolytes - Thomas, R; Penfold, J (American Chemical Society, 2018)
A full comparison of results from binding isotherms and surface tension (ST) measurements on polyelectrolyte (PE)–surfactant (S) mixtures, especially the polymer dependence, shows up clear distinctions between the behavior of two representative PE–S systems, poly(sodium styrenesulfonate) (NaPSS) with dodecyltrimethylammonium bromide (C12TAB) and poly(dimethyldiallylammonium chloride) (PDMDAAC) with sodium dodecylsulfate (SDS) in 100 mM NaCl. The surfactant–monomer binding constant in NaPSS–C12TAB is an order of magnitude greater than that in the PDMDAAC–SDS–NaCl system. This results in the ST behavior being dominated largely by non-cooperativity in the former and by cooperativity in the latter. This leads to the ST in PDMDAAC–SDS–NaCl being at its lowest when the average bound fraction is low but increasing rapidly as saturation approaches. A full analysis is also given of how this is altered in the mixture of PDMDAAC–SDS–NaCl with the nonionic surfactant hexethylene glycol monododecyl ether. In contrast, the much stronger interaction in NaPSS–C12TAB leads to high ST complexes at low bound fractions, whereas the lowest ST occurs near the maximum bound fraction, close to or at precipitation. In the PDMDAAC–SDS–NaCl system, the ST drops to a low value at low surfactant concentrations but then increases to a high value just before precipitation occurs, which, combined with increasing surface adsorption of the free surfactant, results in a sharp ST peak. In the NaPSS–C12TAB system, the ST does not drop until the system is at or close to precipitation and it then stays on a plateau until the point at which free surfactant takes over. Thermodynamics does not allow large step changes in the ST, and it is suggested that where these have been observed they are the result of self-depletion of PE or PE–S complexes on the finely divided precipitate of the complex and are therefore not representative of full equilibrium.